Baseline inflammatory biomarkers identify subgroups of HIV-infected African children with differing responses to antiretroviral therapy - Prendergast, A; Szubert, A; Berejena, C; Pimundu, G; Pala, P; Shonhai, A; Musiime, V; Bwakura-Dangarembizi, M; Poulsom, H; Hunter, P; Musoke, P; Kihembo, M; et al. (Oxford University Press, 2016)
Background: Identifying determinants of morbidity and mortality may help target future interventions for HIV-infected children. Methods: CD4, HIV-1 viral load (VL) and biomarkers (CRP/TNF-/IL-6/sCD14/IL-7) were measured at ART initiation in the ARROW trial (case-cohort design). Cases were deaths, new/recurrent WHO-4 events or immunological non-responders. Results: There were 115 cases (54 deaths, 45 WHO-4 events, 49 immunological non-responders) and 485 controls. Pre-ART, median(IQR) age of cases vs controls was 8.2(4.4-11.4) vs 5.8(2.3-9.3) and CD4% 4%(1-9)vs 13%(8-18). In multivariable logistic regression, cases had lower CD4-for-age (p<0.0001) and higher IL-6 (p=0.002). Clustering biomarkers and CD4-/CD8-for-age identified 4 groups of children: Group-1 had the most cases (41%; 16% died) and profound immunosuppression; Group-2 had similar mortality (23% cases; 15% died), but children were younger, with less profound immunosuppression, high inflammatory biomarkers and VL; Group-3 comprised young children with moderate immunosuppression, high TNF- and CD8-for-age but lower event rates (12% cases; 7% died); Group-4 comprised older children with low inflammatory biomarkers, lower VL and good clinical outcomes (11% cases; 5% died). Conclusions: While immunosuppression is the major determinant of poor outcome on ART, baseline inflammation is an additional important factor, identifying a subgroup of young children with similar mortality. Anti-inflammatory interventions may help improve outcomes.